2012
DOI: 10.1073/pnas.1118880109
|View full text |Cite
|
Sign up to set email alerts
|

Active maintenance of nuclear actin by importin 9 supports transcription

Abstract: Besides its essential and well established role as a component of the cytoskeleton, actin is also present in the cell nucleus, where it has been linked to many processes that control gene expression. For example, nuclear actin regulates the activity of specific transcription factors, associates with all three RNA polymerases, and is a component of many chromatin remodelling complexes. Despite the fact that two export receptors, Crm1 and exportin 6, have been linked to nuclear export of actin, the mechanism by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
335
2
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(362 citation statements)
references
References 50 publications
21
335
2
4
Order By: Relevance
“…These processes are highly dependent on the rearrangements of the F-actin cytoskeleton and the balance between cytoplasmic and nuclear actin pools. Dopie et al confirmed that actin is constantly exported out of the nucleus and that this process is mediated by exportin 6, independently of Crm1 [40]. This contradicts the data presented by Stüven et al that Crm1 plays important role in actin transport from mammalian or insect nuclei [16].…”
Section: Discussioncontrasting
confidence: 53%
“…These processes are highly dependent on the rearrangements of the F-actin cytoskeleton and the balance between cytoplasmic and nuclear actin pools. Dopie et al confirmed that actin is constantly exported out of the nucleus and that this process is mediated by exportin 6, independently of Crm1 [40]. This contradicts the data presented by Stüven et al that Crm1 plays important role in actin transport from mammalian or insect nuclei [16].…”
Section: Discussioncontrasting
confidence: 53%
“…The described feedback loop via cofilin phosphorylation might cause, for example, fluctuations in nucleo-cytoplasmic transport of actin, as dephosphorylated cofilin has been shown to be required for nuclear import of actin (Dopie et al, 2012). Alternatively, this mechanism could also function in the nucleus to regulate gene expression, as both actin (Dopie et al, 2012;Hofmann et al, 2004;Philimonenko et al, 2004) and cofilin (Obrdlik and Percipalle, 2011) have reported roles during transcription. Therefore, Phactr proteins could be yet another example of information transmission between the actin pools in the nucleus and the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…In this assay, nucleus is bleached void of fluorescence and the recovery of fluorescence, which is due to the non-bleached molecules entering the nucleus from the cytoplasm, is observed. The initial recovery, when nuclear reexport is still negligible, can then be used as a measure of nuclear import (Dopie et al, 2012). The nuclear fluorescence of GFPPhactr4 was efficiently recovered after photobleaching (Fig.…”
Section: Localization Of Phactr Proteins In Mammalian Cellsmentioning
confidence: 99%
“…Silencing of CFL1 leads to significantly reduced transcriptional activity, and the association of both RNA polymerase II and actin with gene coding regions is also affected, highlighting the importance of CFL1 as part of the transcriptional apparatus (Obrdlik and Percipalle, 2011). Interestingly, restoring nuclear actin levels independently of cofilin does not restore normal transcription, suggesting that cofilin is not simply controlling transcription through regulation of monomeric actin availability (Dopie et al, 2012).…”
Section: Transcriptionmentioning
confidence: 98%
“…Actin does not have a classic NLS, whereas cofilins have a bipartite NLS that allows for their efficient shuttling into the nucleus (Munsie et al, 2012). Importin-9 interacts with actin in a cofilin-dependent manner (likely to be mediated through the cofilin NLS), and this interaction is crucial for the nuclear transport of actin, which in turn influences the level of transcription (see also below) (Dopie et al, 2012).…”
Section: Nuclear Actin Transportmentioning
confidence: 99%